In-season effect of short-term sprint and power training programs on elite junior soccer players - Mujika, I.; Santisteban, J.; Castagna, C. (The Journal of Strength and Conditioning Research, 2009)
The aim of this study was to examine the effects of 2 in-season short-term sprint and power training protocols on vertical countermovement jump height (with or without arms), sprint (Sprint-15m) speed, and agility (Agility-15m) speed in male elite junior soccer players. Twenty highly trained soccer players (age 18.3 ± 0.6 years, height 177 ± 4 cm, body mass 71.4 ± 6.9 kg, sum skinfolds 48.1 ± 11.4 mm), members of a professional soccer academy, were randomly allocated to either a CONTRAST (n = 10) or SPRINT (n = 10) group. The training intervention consisted of 6 supervised training sessions over 7 weeks, targeting the improvement of the players' speed and power. CONTRAST protocol consisted of alternating heavy-light resistance (15-50% body mass) with soccer-specific drills (small-sided games or technical skills). SPRINT training protocol used line 30-m sprints (2-4 sets of 4 × 30 m with 180 and 90 seconds of recovery, respectively). At baseline no difference between physical test performance was evident between the 2 groups (p > 0.05). No time × training group effect was found for any of the vertical jump and Agility-15m variables (p > 0.05). A time × training group effect was found for Sprint-15m performance with the CONTRAST group showing significantly better scores than the SPRINT group (7.23 ± 0.18 vs. 7.09 ± 0.20 m/s, p < 0.01). In light of these findings CONTRAST training should be preferred to line sprint training in the short term in young elite soccer players when the aim is to improve soccer-specific sprint performance (15 m) during the competitive season.